A Systematics Literature Review of Computational Thinking in Mathematics Education: Benefits and Challenges - Ratri Isharyadi; Dadang Juandi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
Computational thinking (CT) is a leading skill that must be possessed by students and is believed to be one of the keys to future success in a digital society. These skills are often associated with computer science but are now starting to be integrated with other fields of science, including learning mathematics. This literature review aims to study the benefits and challenges of computational thinking (CT) in learning mathematics. This literature review analyzes six references from the Scopus database based on predetermined keywords. Furthermore, content analysis was conducted to see the advantages and challenges of implementing CT in mathematics classes. Based on a literature review, there are several benefits of computational thinking in mathematics class, one of which is that CT improves student performance in learning mathematics; through CT skills, namely generalization and algorithmic thinking, it can help students solve computational problems well, learning that involves CT has the potential to have a positive influence on higher-level thinking skills (logic, algorithmic, and problem-solving views), as well as helping students solve real problems that he found. However, several challenges need to be faced, including the need to pay attention to the duration of learning to improve CT skills, the need for resource readiness which includes teacher competence, teaching materials, and assessment instruments, and teachers need to prepare and design didactic sequences. This literature review is expected to provide educators with an understanding of the extent to which CT can shape mathematics learning to be more creative and meaningful